2022
DOI: 10.1038/s41598-022-06616-7
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal evidence on the development of socioeconomic inequalities in mental health due to the COVID-19 pandemic in Norway

Abstract: The economic and health consequences of the COVID-19 pandemic are unequally distributed. A growing literature finds evidence that those with low socioeconomic status have carried a greater burden in terms of both unemployment and infection risk. Against this background, it is natural to also expect increasing socioeconomic inequalities in mental health. We report from a population-based longitudinal study, assessing the mental health of more than 100,000 Norwegian adults during a period of more than 20 years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 29 publications
3
29
0
Order By: Relevance
“…From a gender perspective, a greater perception of stress by women has emerged. In most studies, the female gender was associated with an increased risk of anxiety and depression [ 59 ], with a very strong correlation confirmed on a large scale [ 60 ]. Suicide attempts also increased significantly more among girls, from three to about five times that of boys (from 99.2 to 146.8/100.000 vs. 32.1–32.3/100.000).…”
Section: Resultsmentioning
confidence: 99%
“…From a gender perspective, a greater perception of stress by women has emerged. In most studies, the female gender was associated with an increased risk of anxiety and depression [ 59 ], with a very strong correlation confirmed on a large scale [ 60 ]. Suicide attempts also increased significantly more among girls, from three to about five times that of boys (from 99.2 to 146.8/100.000 vs. 32.1–32.3/100.000).…”
Section: Resultsmentioning
confidence: 99%
“…The proportion of non-Italian participants in the study was 15.3%. Several studies show that COVID-19 pandemic increased pre-existing social and health-related inequities, and this is also true in the field of mental health ( Gibson et al., 2021 ; Miconi et al., 2021 ; Reme et al., 2022 ; Sommer and DeLisi, 2022 ). There is also evidence that, in some contexts, LAI treatments are disproportionately used in patients of ethnical and cultural minorities: for instance, in the USA they are more used in Black patients than in White patients ( Brown et al., 2014 ; Lawson et al., 2015 ).…”
Section: Discussionmentioning
confidence: 96%
“…Little, however, is known about whether and how this gradient has been exacerbated or mitigated during the COVID-19 pandemic among older adults. Recent studies show a consensus that the COVID-19 pandemic has worsened depression among adults [ 29 , 30 , 31 ]. However, the evidence on the relationship between SEP and depression across different studies was inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…However, the evidence on the relationship between SEP and depression across different studies was inconclusive. Some studies found evidence of a negative association [ 29 ], whilst others suggested that there was no association [ 31 ] or even a positive relationship [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation